2021
DOI: 10.3390/sym13081524
|View full text |Cite
|
Sign up to set email alerts
|

A General Model for Describing the Ovate Leaf Shape

Abstract: Many plant species produce ovate leaves, but there is no general parametric model for describing this shape. Here, we used two empirical nonlinear equations, the beta and Lobry–Rosso–Flandrois (LRF) equations, and their modified forms (referred to as the Mbeta and MLRF equations for convenience), to generate bilaterally symmetrical curves along the x-axis to form ovate leaf shapes. In order to evaluate which of these four equations best describes the ovate leaf shape, we used 14 leaves from 7 Neocinnamomum spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…When two axially symmetrical rate equations along the x-axis are combined into one, we find that it can describe and fit a variety of ovate leaf shapes especially well. 19 Therefore, we added three rate equations to 'biogeom' . The three rate equations can be used to produce sigmoid curves by integration.…”
Section: Rate Equations and Their Extensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When two axially symmetrical rate equations along the x-axis are combined into one, we find that it can describe and fit a variety of ovate leaf shapes especially well. 19 Therefore, we added three rate equations to 'biogeom' . The three rate equations can be used to produce sigmoid curves by integration.…”
Section: Rate Equations and Their Extensionsmentioning
confidence: 99%
“…In addition, because of the high degree of leaf-shape variation for ovate leaves (i.e., variations in the curvature of leaf boundaries across different plant species), this class of leaf shapes cannot be accurately represented by the Gielis equation, and additional equations are needed to describe such variations. 19 In thermal biology, many temperature-dependent development models are used to reflect the effect of temperature on organismal developmental rates (i.e., the reciprocal of the developmental time required to complete a specific developmental stage). Prior studies have shown that the integral forms of temperature-dependent developmental (or growth) rate models can produce sigmoid growth curves, which can be used to describe the growth trajectories of many animals and plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the MBE is flexible in fitting a skewed bell-shaped curve, it is potentially useful to model the profiles of ovate leaves [32]. Shi et al [32] formed two axially symmetrical curves using the modified beta equation (also the modified LRF equation) to fit the ovate leaf shapes of Neocinnamomum plants (Lauraceae). Given that the MBE can generate similar skewed curves, the MBE should be similarly useful in describing ovate leaf shape.…”
Section: Other Potential Applications Of the Modified Brière Equationmentioning
confidence: 99%
“…It cannot be used to accurately evaluate the degree of leaf bilateral asymmetry, or predict the leaf centroid from the base of an oval or oboval leaf shape. In order to cope with this limitation, Shi et al (2021b) developed an ovate and obovate leaf shape model using leaf length and width and a third parameter representing the distance from the leaf base to the point on the leaf length axis associated with maximum leaf width. Consequently, Li et al (2021c) defined the “centroid ratio” (as the ratio of this third parameter to leaf length) to quantify the extent of the deviation of the leaf centroid from the midpoint of leaf length.…”
Section: Introductionmentioning
confidence: 99%